3D printed cylindrical capsules as a Chlorella pyrenoidosa immobilization device for removal of lead ions contamination - Lan, Shuzhen; Xia, Xinshu; Liu, Zhen; Yang, Yujin; Qian, Qingrong; Luo, Yongjin; Chen, Qinghua; Cao, Changlin; Xiao, Liren (Frontiers in Chemistry, 2022)
Immobilization is considered as a promising strategy toward the practical applications of powdered adsorbent. Herein, three dimensional (3D) printing cylindrical capsules with cross-linked PVA hydrogels membrane in encapsulate Chlorella pyrenoidosa (Cp) were utilized for removal of lead ions. The chemical compositions, hydrogels performance and morphologies of the membranes were determined by Fourier transformed infrared spectroscopy (FTIR), cross-linking degree, swelling degree, membrane flux and scanning electron microscopy (SEM). It is found that PVA cross-linking structure is successfully synthesized on the surface of capsule body and cap due to the presence of PVA in the filament. The lead ions adsorption capacity related to initial concentration of 50 mg/L in 48 h is reached 75.61%, revealing a good removal ability. The self-floating 3D printed capsules device also shows an excellent recovering property. After 7 runs of adsorption experiment, the lead ions adsorption ratio remains 78.56%, which will bring a broad prospect in wastewater treatment, chemical slow release along with sample preparation and separation.